2021
DOI: 10.1017/s0376892921000138
|View full text |Cite
|
Sign up to set email alerts
|

Spatial conservation prioritization considering socioeconomic costs and degradation conditions in the Southwest China Biodiversity Hotspot

Abstract: Summary There have been calls for the expansion of protected areas (PAs) to tackle the ongoing biodiversity loss, yet it is unclear where future PAs might help to protect biodiversity in degraded landscapes under the conservation planning principles of complementarity, connectivity and cost-effectiveness. Our conservation goal is to increase the PA network coverage to up to 30% of the landscape of the Zhangjiang River Basin for target species in the karst area of southwest China, a global biodiversity hotsp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Nonetheless, biodiversity conservation prioritization sometimes unintentionally sets aside the influence of exotic species. For example, biodiversity hotspots were prioritized in southwestern China by integrating socio‐economic costs (Fu et al ., 2021), but it was reported that many exotic species have colonized this area, including crofton weed Eupatorium adenophora (Lu & Ma, 2005), Siam weed Chromolaena odorata (Shi et al ., 2021) and water hyacinth Eichhornia crassipes . Conservation prioritization of plant biodiversity has been studied in Norway by incorporating an indicator of “threat,” which only refers to timber harvest profitability, but we are also informed by the existence of some invasive plants in Norway such as Persian hogweed Heracleum persicum (Meier et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, biodiversity conservation prioritization sometimes unintentionally sets aside the influence of exotic species. For example, biodiversity hotspots were prioritized in southwestern China by integrating socio‐economic costs (Fu et al ., 2021), but it was reported that many exotic species have colonized this area, including crofton weed Eupatorium adenophora (Lu & Ma, 2005), Siam weed Chromolaena odorata (Shi et al ., 2021) and water hyacinth Eichhornia crassipes . Conservation prioritization of plant biodiversity has been studied in Norway by incorporating an indicator of “threat,” which only refers to timber harvest profitability, but we are also informed by the existence of some invasive plants in Norway such as Persian hogweed Heracleum persicum (Meier et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%